2007
DOI: 10.1007/s10096-007-0334-0
|View full text |Cite
|
Sign up to set email alerts
|

Panton-Valentine leukocidin genes and staphylococcal chromosomal cassette mec types amongst Finnish community-acquired methicillin-resistant Staphylococcus aureus strains, 1997–1999

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) strains from Finland covering years 1997-1999 were studied for the presence of Panton-Valentine leukocidin (PVL) gene loci, and the clinically well-defined community-acquired MRSA (CA-MRSA) strains (n = 108) also for staphylococcal chromosomal cassette mec (SCCmec) and multilocus sequence types (MLST). Only a minority (12%) of the CA-MRSA strains contained the PVL gene loci and possessed genotypes formerly described as typical to CA-MRSA strains. The majority … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Several studies have reported the pvl as a reliable marker for CA-MRSA strains 15 16 and a few studies 17 18 have reported the presence of the PVL toxin more in MSSA than MRSA. Our finding is in agreement with the reports from Ireland 19 and Finland 20 .…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have reported the pvl as a reliable marker for CA-MRSA strains 15 16 and a few studies 17 18 have reported the presence of the PVL toxin more in MSSA than MRSA. Our finding is in agreement with the reports from Ireland 19 and Finland 20 .…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies also have shown variations in SCCmec cassettes. These include (i) strains containing both SCCmec type IV and ccrC, (ii) strains carrying multiple ccr genes (3,7,14,26), (iii) strains carrying ccr genes without a mec complex, (iv) strains carrying a mec complex without ccr genes, and (v) a mecA-positive MRSA strain with neither ccr genes nor a mec complex (3,25,26). In our study, only mecA from three MR-CNS strains could be detected.…”
Section: Discussionmentioning
confidence: 48%
“…During 1997 to 1999, only one PVL-positive strain type (FIN-11, ST80: IV, t044) was community associated (5). In the present study, a USA300 variant (FIN-25, ST8;IV, t008) which first appeared in 2004 was the third most common CA-MRSA strain type.…”
mentioning
confidence: 41%